Influence of thermal diffusion on unsteady MHD free convective, chemically reactive, and radiating flow past a semi-infinite inclined moving plate in a porous medium with arbitrary ramped temperature (Journal of Naval Architecture and Marine Engineering, 2025)
The present paper aims to investigate the effect of thermal diffusion in a free convective, radiative, viscous, chemically reacting, incompressible, and unsteady MHD flow past an exponentially accelerated moving inclined plate submerged in a porous medium. The fluid is taken as optically thick and non-gray. A uniform magnetic field is applied in the transverse direction of the plate. The ramped temperature effect is also considered. The radiative heat flux that appears in the energy equation is described by the Rosseland approximation method. A closed form of the Laplace transformation technique is adopted to obtain analytical solutions to the non-dimensional governing equations. A detailed discussion on the effects of various governing parameters on the velocity field, temperature field, concentration field, Nusselt number, Sherwood number, and skin friction are analyzed using suitable graphs and tables. The investigation shows that the Soret effect hikes both concentration and velocity of the fluid. The chemical reaction effect upsurges the process of mass transfer from the plate to the fluid.Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 81-98